Urban Kano Insecurity: A Study Proposal of Five Factor Analysis - Siro, Ali Ado; Sundramoorthy, P. (School of Social Sciences, 2015)
Fear, anxiety and hopeless future are some major characteristics in most parts of the developing world. Perhaps the genesis is traced to poor public leadership. This gives rise to absence of rule of law. As a societal pillar, poor governance results in other negative effects such as unemployment, poverty, law enforcement corruption and police inadequacies. These factors are alleged to be most significant in triggering societal insecurity. It is in this context that the literature argued on the impact of these factors in causing human insecurity. The write up is a proposal paper of a PhD research being conducted in urban Kano, Nigeria. Although there are numerous issues related but these five are considered to be the most crucial. Hence, the findings are expected to indicate possible relationship with insecurity of urban Kano. The research is to be guided by Broken Windows theory (Wilson and Kelling, 1982). Meanwhile, innovative solutions may need to be initiated. An obligation that demands the participation of the general public.